Innovation Capability and Learning Capability To Individual Performace : Well Being Moderation (Case Study of Small and Medium Enterprises: Freez Food Baby Porridge Sedati) - Fransisca Eri Yulianti; Wahyu Eko Pujianto (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2024)
This study aims to investigate the relationship between innovation capability, learning capability, and individual performance in Small and Medium Enterprises (SMEs) with well-being moderation, using the Case Study of "Freez Food Baby Porridge Sedat" product. A survey method was employed to collect data from 30 respondents comprising owners and employees of these SMEs. The analysis results indicate that innovation capability has a significant positive influence on individual performance through learning capability. Additionally, individual well-being moderates the relationship between innovation capability, learning capability, and individual performance. The practical implications of these findings underscore the importance for SMEs to develop innovation and learning capabilities as strategies to enhance individual performance, while considering well-being as a moderating variable. This study offers valuable insights for SME owners in designing human resource development programs focused on improving individual performance through investments in innovation and learning.